2023
DOI: 10.1037/pspp0000466
|View full text |Cite
|
Sign up to set email alerts
|

Transactional effects between personality and religiosity.

Abstract: Do changes in religiosity beget changes in personality, or do changes in personality precede changes in religiosity? Existing evidence supports longitudinal associations between personality and religiosity at the between-person level, such that individual differences in personality predict subsequent individual differences in change in religiosity. However, no research to date has examined whether within-person changes in personality lead to subsequent changes in religiosity. Using random intercept cross-lagge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The full data are available on request at https://www.lissd ata.nl/. We have used data from this panel to examine questions about the development of personality differences and religiosity (e.g., Entringer et al, 2023;Lenhausen et al, 2023;Olaru et al, 2023). No previous research has used these data to examine psychological change before and after religious conversion and deconversion, which was the primary goal of this study.…”
Section: Transparency and Opennessmentioning
confidence: 99%
See 1 more Smart Citation
“…The full data are available on request at https://www.lissd ata.nl/. We have used data from this panel to examine questions about the development of personality differences and religiosity (e.g., Entringer et al, 2023;Lenhausen et al, 2023;Olaru et al, 2023). No previous research has used these data to examine psychological change before and after religious conversion and deconversion, which was the primary goal of this study.…”
Section: Transparency and Opennessmentioning
confidence: 99%
“…At every wave, we assessed three indicators of participants' religious beliefs and practice: (1) belief in God, (2) the frequency with which participants attended religious gatherings, and (3) the frequency with which they prayed (see also, Bleidorn et al, 2022;Entringer et al, 2023;Lenhausen et al, 2023). Specifically, participants reported their belief in God using the item "Which of the following statements best matches your idea of God?"…”
Section: Religious Beliefs and Practicementioning
confidence: 99%
“…Study by Javeed and Shaikh (2010) showed that there is a significant positive relation between extraversion Introversion and self-esteem. There is significant positive relation between Introversion and religiosity (Lenhausen, et al, 2023). Mancini, et al, (2023) saw the relationship between religious coping strategies and social anxiety.…”
Section: Relationship Between Parental Self-esteem Extraversion Intro...mentioning
confidence: 99%